SOME QUESTIONS ABOUT DEPENDENCE OF THE FEDERAL BUDGET BALANCE ON THE QUALITY OF BUDGET PLANNING - G. N. Kutsuri (Publishing House of the State University of Management, 2020)
The problem of the quality of budget planning and its impact on the balance of the federal budget has been raised. Attention to the complexity of scientific justification of the proportions of budgeted funds due to their high dependence on a large number of both internal and external macroeconomic factors, including those that are difficult to predict has been drawn. The principles that should be underlying the identification and assessment of risks of the federal budget balance as well as the quality of budget planning and forecasting indicators that can affect the balance and stability of the federal budget in strategic perspective have been reviewed and systematized. It has been offered that the Federal budget planning should be based on parameters that meet the principles of goal setting and realism.